The process of Neolithisation in South-eastern Europe - Budja, Mihael (Documenta Praehistorica, 2005)
Paper discusses concepts of 'neolithic package', 'demic diffusion' and 'revolution of symbols' in relation to the process of Neolithisation in South-eastern Europe and the phylogeography of Y chromosome haplogroups I1b*, J and E. It is suggested that 'demic diffusion' is not a realistic scenario, and that there were two Neolithisation trajectories and two related, archaeologically and genetically readable, regional palimpsests in South-eastern Europe.
Keywords: archaeology; arheologija; neolitik; nabiralništvo; poljedelstvo; simbolizem; družbeni razvoj; genetics; genetika